Do ESG Score and Cash Holding Drive Firm Value? Insights from Institutional Ownership in Indonesia - Reza Virly Alfriansyach; Regina Jansen Arsjah (Manunggal Halim Jaya, 2026)
This study examines the effect of ESG score and cash holding on firm value, as well as the moderating role of institutional ownership, using a sample of 91 energy companies listed on the Indonesia Stock Exchange (IDX) during 2021–2024. ESG performance is measured through content analysis based on 93 GRI disclosure indicators. At the same time, firm value is proxied by Tobin's Q. Using unbalanced panel data and Random Effects Model estimation, the findings reveal that ESG scores do not significantly influence firm value, indicating that the Indonesian capital market has not yet fully valued sustainability initiatives as a driver of corporate value. In contrast, cash holding demonstrates a strong positive effect, suggesting that liquidity remains a critical financial signal in the energy sector, which is characterized by high volatility and substantial investment needs. The moderating analyses show that institutional ownership does not strengthen the ESG value relationship and even weakens the positive impact of cash holding on firm value, reflecting the passive monitoring role of institutional investors in emerging markets. Overall, the study provides empirical evidence that firm value in Indonesia is more sensitive to financial fundamentals than sustainability practices, while external governance mechanisms remain limited in effectiveness. These insights contribute to the corporate governance and sustainable finance literature and offer practical implications for companies, investors, and regulators regarding the strategic integration of ESG and financial policies.